2014
DOI: 10.1038/cddis.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

miRNA let-7e targeting MMP9 is involved in adipose-derived stem cell differentiation toward epithelia

Abstract: miRNA let-7e is involved in stem cell differentiation, and metalloproteinases are among its potential target genes. We hypothesized that the inhibitory action of let-7e on regulation of MMP9 expression could represent a crucial mechanism during differentiation of adipose-derived stem cells (ASCs). ASCs were differentiated with all-trans retinoic acid (ATRA) to promote differentiation, and the effect of let-7 silencing during differentiation was tested. Results indicate that ASCs cultured with ATRA differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…Peptides (P17 and P144) targeting EMT also inhibit the expression of CD44 and SOX2 [41]. Keratin 18 is considered as a differentiation and epithelial marker, indicating differentiation and mesenchymal-epithelial transition (MET) of breast cancer cells [42, 43], while Vimentin functions as a dedifferentiation and mesenchymal marker in breast cancer cells [44, 45]. In the present study, we found that flubendazole treated MDA-MB-231 cells expressed high level of Keratin 18 and low level of β-catenin, N-cadherin and Vimentin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides (P17 and P144) targeting EMT also inhibit the expression of CD44 and SOX2 [41]. Keratin 18 is considered as a differentiation and epithelial marker, indicating differentiation and mesenchymal-epithelial transition (MET) of breast cancer cells [42, 43], while Vimentin functions as a dedifferentiation and mesenchymal marker in breast cancer cells [44, 45]. In the present study, we found that flubendazole treated MDA-MB-231 cells expressed high level of Keratin 18 and low level of β-catenin, N-cadherin and Vimentin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to find a link between miR-98, E2F5 and the TGFB regulation of myogenesis. let-7 miRNAs, which influence the timing of Caenorhabditis elegans development, have been implicated in regulating cell proliferation and differentiation of numerous cell and tissue types, such as neuronal, cardiac, adipogenic and others ( [17][18][19][20][21], reviewed in [3]) in mammals. In a few cases, a let-7 miRNA acted as a negative regulator of differentiation, via an unknown mechanism [22].…”
Section: E2f5 Directly Down-regulates the Differentiation Inhibitors mentioning
confidence: 99%
“…The immunofluorescence confirmed that rEPCs could be differentiated from rADSCs. According to the data from the literature and this study, isolating ADSCs from patients for clinical applications has great potential. The morphology of the PCL scaffolds observed by SEM showed that their fiber diameters were in the submicron range, which fulfilled the necessity of mimicking the ECM and contributed to the cell attachment and proliferation for the regeneration of the natural tissues.…”
Section: Discussionmentioning
confidence: 92%